Diversity and inclusion in organizations - Stone, Dianna L., 1947-; Dulebohn, James H.; Lukaszewski, Kimberly M. (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"The population of many nations around the world are becoming increasingly diverse (Stone-Romero, Stone, & Salas, 2003). For example, recent reports estimate that by 2060 the U. S. will become a majority minority nation (i.e., ethnic minorities including African-Americans and Hispanic-Americans will represent the majority of the population) (U. S. Bureau of Census, 2019). As a result, many U. S. and worldwide organizations will employ large number of ethnic minority group members, and will face numerous challenges associated with attracting, motivating, and retaining employees who are culturally diverse. In view of the growing cultural diversity in worldwide organizations, the primary goals of this issue are to (a) advance theory and research on diversity and inclusion in organizations, (b) present new theoretical frameworks to foster future research, and (c) consider a variety of diversity-related issues that have key implications for research and practice. It includes twelve very interesting articles that focus on an array of diversity-related issues including multiculturalism, gender, stereotypes of racial minorities, effect sizes in diversity research, diversity training, LGBT issues, age, and racial harassment, etc. For example, the first article by Dianna Stone, James Dulebohn, and Kimberly Lukaszewski discusses how differences in the cultural values of four U. S. ethnic minority groups (e.g., African-Americans, Hispanic-Americans) will influence HR policies and practices. The second article by George Dreher, Aarti Ramaswami, and Thomas Dougherty focuses on a very important issue, and considers the extent to which a life partner can act as a career catalyst (or inhibitor) and contribute to women's career attainment. The next article by Eugene Stone-Romero, Dianna Stone, Mark Hartman, and Megumi Hosoda examines the stereotypes of six ethnic groups (e.g., African-American, Mexican-American, Native American, etc.). Their results are intriguing and revealed that Anglo-Americans, Chinese-Americans, Native-Americans, and East Indian Americans were viewed most positively whereas African-American and Mexican American were viewed most negatively"-- Provided by publisher.
Keywords: Diversity in the workplace.; Multiculturalism.; Minorities -- Employment.; Business & Economics -- Human Resources & Personnel Management.; Business ethics and social responsibility.; Personnel and human resources management.; elektronické knihy; electronic books